Enhanced storage stability and in-vitro digestibility of powdered-solid lipid nanoparticles with high-algae oil-load - Zhao, Jiahe; Liu, Yuanyuan; Shen, Cai; Lai, Oi-Ming; Tan, Chin Ping; Cheong, Lingzhi (Elsevier, 2023)
Algae oil is the primary natural source of docosahexaenoic acid (DHA), which is a type of omega-3 polyunsaturated fatty acids with many healthful properties. However, it is prone to oxidation and degradation. The present study aimed to design and prepare powdered-solid lipid nanoparticles (SLNs) with high algae oil load (>300 mg/g powder) using palmitic acid, protein (sodium caseinate or whey protein isolate) and (2-Hydroxypropyl)-²-cyclodextrin. All of the spray-dried powdered SLNs were mostly spherical (2 to 10 ¼m). Our results showed palmitic acid had a significant effect on the storage stability and in-vitro digestibility of the powdered SLNs. Palmitic acid content enhanced the storage stability of the powdered SLNs with low increases in peroxide and p-anisidine values during the accelerated storage test. Unsaturated oils encapsulated within the solid lipids (palmitic acids) crystalline matrix structure could prevent contact of oxidation agents with unsaturated fats. Additionally, powdered SLNs with high concentration of palmitic acids showed a high release of total titratable acids as well as high DHA hydrolysis efficiency, indicating higher in-vitro digestibility.